Desempenho agronômico de cultivares de Coffea arabica L. após o “Esqueletamento/Safra Zero” - Domingues, Cleiton Gonçalves (2020)
The use of cultivars resistant to diseases has been important in their control, as the damage caused by diseases can bring significant losses to the crop, reducing productivity, due to the marked depletion in plants. Currently, in the management of coffee plantations, skeleton-type pruning has been used for crop renewal, with the elimination of unproductive plant tissues, favoring high productivity. The adoption of the “Safra Zero” system started to be adopted in order to maintain the size of the crop and eliminate the harvests in a low crop year, recommending pruning cycles after years of high crop. Thus, the aim of this work was to identify Arabica coffee cultivars that are more productive and responsive to skeleton-type pruning. An experiment was installed in the experimental area of the Department of Agriculture, Coffee Sector of the Federal University of Lavras (UFLA), in December 2005. The experimental design used was randomized blocks, with 25 cultivars of Coffea arabica L., 23 supposedly resistant to rust and two susceptible commercial witnesses (Topázio MG 1190 and Catuaí Vermelho IAC 144) with three repetitions with spacing of 3.5 x 0.7 m and plots of 12 plants. In 2014, the first cycle of skeleton pruning was carried out, and the second cycle was carried out in August 2016. In 2018, productivity, percentage of chochos fruits, percentage of ripe, green and dry fruits, vegetative vigor, were evaluated. incidence of rust and cercosporiosis. The data obtained were analyzed using the Genes program, performing the analysis of variance at 5% significance using the F test and for the grouping of means, the Scott-Knott test was used. The cultivar Catucaí Amarelo 20/15 hp 479 shows high productivity in the conventional system and in the “Safra Zero” system and a good percentage of fruit ripening at the time of harvest, however, disease control is necessary. The cultivars Palma II, Pau Brasil MG 1 and IPR 103 are highly productive and recover after skeletal pruning. With emphasis on Palma II, which presented resistance to rust disease and average values for cercosporiosis. This is the most suitable for planting in mountain regions.